Breadfruit (Artocarpus altilis) starch-based nanoparticle formation through dropwise mixing nanoprecipitation - Harsanto, B.W.; Pranoto, Yudi; Supriyanto, Supriyanto; Kartini, Indrianti (Rynnye Lyan Resources, 2022)
Starch nanoparticles from breadfruit (Artocarpus altilis) have been prepared using nanoprecipitation. The study aimed to investigate the performance of dropwise and direct mixing of ethanol as a non-solvent in the presence of and without surfactant (Tween 80) into breadfruit suspension during nanoprecipitation. The resulting breadfruit starch nanoparticles were evaluated for particle size and shape by particle size analysis, transmission electron microscopy (TEM), and scanning electron microscopy (SEM), crystal pattern by X-ray diffraction (XRD), and functional group by FTIR spectrophotometer. It was observed that performing the dropwise mixing technique without Tween 80 produced particles in the nanometer scale (175 nm), with uniform size distribution (18-459 nm), a porous surface, and an amorphous phase (single XRD peak at 19o). These breadfruit starch nanoparticles pave the way for incorporating starch products into a wide array of industry-application.